(untitled) (Research, Society and Development, 2021)
The COVID-19 pandemic is an unexpected historical event with an impact on all aspects of life - especially those of an occupational and mental nature. In a few months, it has altered daily life and social relations and, in addition to social distancing, isolation or quarantine, the world’s population has to live with fear, insecurity and human and economic losses. Young people, particularly young women with a psychiatric history and no social support, are more vulnerable to the psycho-emotional consequences of the pandemic. The objective of this study was to observe the impact of COVID-19 on the mental health of students and their coping strategies. This was an observational study with a quantitative and cross-sectional method. The sample consisted of health students from a public university in the state of Paraíba, Brazil. Participants were recruited from the digital platforms in June 2020, a period of social isolation. The link to the Google forms questionnaire was made available on Instagram and WhatsApp. A total of 56 students, most of them women, answered the questionnaire. The most prevalent symptoms during social isolation were anxiety (76.8%), concern (71.4%), fear (62.5%), insomnia (60.7%) and sadness (55.4%). Anxiety, depression, and hopelessness symptoms were more prevalent in younger female students with negative health perception. Complementary therapies and conversations with friends and family stand out as coping strategies. Mental health demands a convergence of efforts and institutional actions are needed to manage the psycho-emotional and neurobiological impact of COVID-19 in an integrated and integral way.